Policy against inflation - Harrod, Roy (London : Macmillan : New York : St. Martin's Press, 1958)
The book examines the definite principles of monetary policy, inflation and foreign exchange policy and their influence in shaping the economic growth of a country like Britain.
Includes index
includes bibliographical footnotes
usc 24/07/2017
Loans
Keywords: Inflation (Finance); Currency question; Great Britain